Research of Increase of the Wear Resistance of Machine Parts and Tools by Surface Alloying - D.D. Marchenko; K.S. Matvyeyeva (Проблеми трибології, 2023)
The work scientifically substantiates the application of an effective technology for increasing the wear resistance of machine parts and tools due to complex diffusion saturation of the surface layer of parts made of iron-carbon alloys in the process of casting on gasified models based on the optimization of the composition of saturating mixtures and the establishment of patterns of structure formation.